Separation and Simultaneous Determination of Pb(II) and UO2(II) Using a Ligand Containing Mobile Phase in Reversed-Phase High Performance Liquid Chromatography - Soleimani, Majid; Morsali, Ali; Ghahreman Afshar, Majid (Asian Journal of Chemistry, 2011)
Separation and determination of Pb(II) and UO2(II) was performed by a simple, isocratic, reversed phase high performance liquid chromatography using mobile phase containing 1,4- bis-(4-pyridyl)-2,3-diazo-1,3-butadiene (4-bpdb) as a ligand. The resolution was determined with various ligand concentrations as well as the ratio of methanol in aqueous mobile phase at different pH values. The effect of ionic salts, type and concentration of buffer on the separation is also discussed. The results showed that a good separation was obtained at 25 ºC, using a mobile phase containing 0.05 mM (4-bpdb), 30 mM acetate buffer and 20 % methanol at pH 6.5. The response was linear from 0.1 to 0.5 mM with a detection limit of 5.8916 × 10-3 mM for Pb(II) and 15 to 25 mM with a detection limit of 0.2626 m M for UO2(II), respectively.